2019
DOI: 10.1016/j.molcel.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Landscape of PCGF Proteins Reveals Both RING1A/B-Dependent-and RING1A/B-Independent-Specific Activities

Abstract: Summary Polycomb repressive complexes 1 and 2 (PRC1 and PRC2) control cell identity by establishing facultative heterochromatin repressive domains at common sets of target genes. PRC1, which deposits H2Aub1 through the E3 ligases RING1A/B, forms six biochemically distinct subcomplexes depending on the assembled PCGF protein (PCGF1–PCGF6); however, it is yet unclear whether these subcomplexes have also specific activities. Here we show that PCGF1 and PCGF2 largely compensate for each other, while oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
219
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(239 citation statements)
references
References 60 publications
(84 reference statements)
15
219
2
3
Order By: Relevance
“…Nonetheless, it remains unclear to what extent this developmental delay is directly caused by the lack of maintenance of target gene repression. Moreover, the hypomorphic properties of the RING1B I53A mutant (Tsuboi et al, 2018) The work of several laboratories including ours have also highlighted that mammalian PRC1 exist in distinct biochemical forms (Gao et al, 2012) that are not exclusively associated with transcriptional repression (Fursova et al, 2019;Scelfo et al, 2019). Actively transcribed sites are specifically associated with PRC1.1, PRC1.3 or PRC1.6 forms.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Nonetheless, it remains unclear to what extent this developmental delay is directly caused by the lack of maintenance of target gene repression. Moreover, the hypomorphic properties of the RING1B I53A mutant (Tsuboi et al, 2018) The work of several laboratories including ours have also highlighted that mammalian PRC1 exist in distinct biochemical forms (Gao et al, 2012) that are not exclusively associated with transcriptional repression (Fursova et al, 2019;Scelfo et al, 2019). Actively transcribed sites are specifically associated with PRC1.1, PRC1.3 or PRC1.6 forms.…”
Section: Discussionmentioning
confidence: 82%
“…Here we have developed a simple model that generates inducible expression of a fully catalytically inactive form of RING1B (RING1B I53S in a RING1A null background) to dissect the contribution of H2AK119ub1 deposition to the structural properties of PRC1. This system allows monitoring of the acute effects induced by the loss of H2AK119ub1 deposition by preventing transcriptional adaptations and indirect effects that occur in constitutive PcG mutant ESC maintained in pluripotent conditions (Fursova et al, 2019;Scelfo et al, 2019). With this system, we showed that the expression of the catalytic inactive RING1B I53S neither affected the assembly of distinct PRC1 subcomplexes, nor its ability to associate with target promoters, but it did fail to maintain transcriptional repression of target genes to an identical extent as global RING1A/B deletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mechanistic link between CGIs and Polycomb recruitment came with the discovery that KDM2B, a component of the PCGF1containing vPRC1 complex, has DNA binding activity which is specific for non-methylated CpG dinucleotides, suggesting that recognition of CGI DNA may underpin Polycomb target site selection He et al, 2013;Wu et al, 2013). Similarly, the PCGF6-containing vPRC1 complex has DNA binding activities that contribute to Polycomb occupancy in specialised contexts (Endoh et al, 2017;Zdzieblo et al, 2014) or more generally Scelfo et al, 2019;Yang et al, 2016). However, while PCGF1 and PCGF6 broadly occupy target sites, somewhat paradoxically only a subset of these achieve high levels of PRC1, H2AK119ub1, PRC2 and H3K27me3 ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of H2A ubiquitination is mediated by the noncanonical complexes (42) while only the canonical complexes can be recruited by H3K27me3 through their CBX subunit (15,16,43) and have the ability to mediate both local compaction and long range interactions (6, 10-12, 44, 45). While complete loss of PRC1 via deletion of RING1A/B is lethal (46,47), different PRC1 complexes can have distinct roles, owing to both the different subunits but also tissue specific expression of complex members (19,22,39,(48)(49)(50)(51)(52)(53)(54)(55)(56). In Drosophila, in addition to the canonical complex outlined above, two non-canonical PRC1 complexes have been described: dRAF, which contains KDM2, a lysine demethylase subunit (57), and a complex which contains an alternative Psc homolog (58).…”
Section: Introductionmentioning
confidence: 99%